Amphibians and reptiles (Herpetofauna) of the plant associations of the Laguna Gandoca, Limón, Costa Rica - Estrella-Morales, Josimar (2018)
The amphibians and reptiles in coastal areas shows changing patterns of distribution and number of individuals, influenced by environmental physical and chemical factors. The objective of this study was to characterize the community of herpetofauna in the plant associations surrounding the Gandoca Lagoon, during rainy period. The evaluation took place in July 2010, in the mangrove, raffia and forest associations. Four band transects (10 m x 3 m) were traced in each plant association, and two samples were taken out per day and two per night from each transect, using the method of intensive search. The individuals were identified; Temperature, vegetation cover, soil moisture and litter depth were measured. Equity, diversity and dominance of species, so as heterogeneity among the plant associations were determined using the program and Richness BioDiversity Pro 4. A total of 27 species were founded (18 in raffia, 17 in forest, and 4 in mangrove). The highest equity value, H = 2,47, and the lowest dominance, d = 0,18, were identified in the forest. Forest and raffia showed the highest similarity, 0,63. The vegetation surrounding the Gandoca Lagoon was at that time a transitional one, from mangrove to a- well established forest, with a large area of swamp palm (Rhaphia taedigera), which was mixed with forest vegetation. That conformation explains the similarity in the values of diversity between Raffia and forest. These partnerships provided microhabitats and resources to reptiles and amphibians, while the mangrove forest, underutilized, was important for species as the Tretanorhinus nigroleteus, with specialized habits.